Persepsi Kepala Sekolah Terhadap Kinerja Guru Pendidikan Jasmani Olahraga dan Kesehatan Di Sma Negeri Se-Kota Lubuklinggau - Gilang Permadi; Muhammad Suhdy; Ever Sovensi (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2021)
This study aims to determine the Principal's perception of the performance of physical education teachers in SMA Negeri in Lubuklinggau City. This research is a descriptive study with one variable without making comparisons or connecting with other variables. The sample consisted of 9 principals with a sampling technique using non-probability sampling. Data collection in the study used a closed questionnaire of 33 statement items. It consists of 4 competencies, namely personality, pedagogic, professional, and social. The results of this study are the Principal's perception of the performance of the Penjasorkes teacher at the State High School in Lubuklinggau City for the perception category of